How mothers talk about their relationship with their young sons following intimate partner violence and the implications for intergenerational prevention and systemic intervention. Issue 2 (5th May 2023) - Nankivell, Louise; Taggart, Danny
The aim of this study was to understand how women describe their relationship with their young son(s) in a context of and following intimate partner violence. Face-to-face interviews with eight women were conducted. The analysis suggested that women constructed violence as being a cycle and their relationship with their son was impacted by this in multiple ways. The paper critically draws on attachment, family systems and trauma literature to consider the data in context, and offers a range of clinical implications for practice, training and supervision.